VISIT VISA ACTIVITIES BUSINESS SPEAKER SUBJECT AND SUPERVISION - Harits Rafi Putra Pradana; Kadek Sintya Anjani; Yoga Tri Hartanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Migration Regulation Number 6 of 2011, which regulates all kinds of movements related to people's affairs both inside and outside the Indonesian Territory. Indonesia adheres to a certain strategy in which every outsider who enters the territory of Indonesia is obliged to be valuable and not endanger the interests and normal strength of the state, in an effort to maintain the security of the nation's power. Stay Permit Extension, Termination, Cancellation, and Termination of Stay Permits Owned by Outsiders, Guidelines for Priest Regulations and Basic Freedoms Number 24 of 2016 concerning Procedures for Application and Issuance of Short Visas and Visit Visas. The management of the movement of the presence and training of foreign nationals in the territory of Indonesia is an action that combines the coordination, arrangement, and prosecution of foreign nationals in the territory of Indonesia. Regulation No. 6 of 2011, particularly regarding the sorting, handling and display of information and movement data as well as the basis for the list of names of outsiders that can be fought and avoided, regulatory oversight of the presence and activities of outsiders, as well as various biometric information.